Pola Makan dan Pertumbuhan Bobot Tubuh Tikus yang Diinokulasi Porphyromonas gingivalis Sebelum dan Sesudah Terjadinya Periodontitis - Praptiwi Praptiwi; Enik Sulistyowati; Kustiyono Kustiyono (MEDIA MEDIKA INDONESIANA, 2009)
Food pattern and body weight growth of rat inoculation by porphyromonas gingivalis before and after periodontitisBackground: The rat model of periodontitis induced by Porphyromonas gingivalis (P. gingivalis) were selected to prove that energy requirement is rising in periodontitis, as well as the body mass erosion that giving influence to growth. This study aimed to get food consumption pattern and the lowest growth of body weight which would give information about time period to deliver nutrients needed to increase body weight to fasten healing.Methods: Experimental study was done using 63 Wistar adult, healthy male rat in Laboratorium Penelitian dan Pengujian Terpadu Gadjah Mada University, Yogyakarta in 2007-2008. The subject study were induced periodontitis by bacterial innoculation using P. gingivalis. The objects of the study were food consumption pattern and growth of body weight. Food consumption pattern was percentage of subject finishing food devided by total subject, before and during periodontitis period. Growth of body weight is mean of increasing body weight of 2 adjacent periodontitis period devided by length of day between the 2 periods.Results: The beginning of subject finishing the food was the time when periodontitis identified by Pathology Anatomic examination. Amount of subject finishing the food was variable according to periodontitis process. The growth of body weight before and during periodontitis was inclining by age. The highest incremental of mean body weight per day was observed before periodontitis until the beginning of periodontitis. The lowest incremental of mean body weight was found between the beginning of periodontitis tochronical period 1, as long as 7 days.Conclusions: The subject study began to finish the food since the beginning of periodontitis. During 7 days period from the beginning of periodontitis to chronical period 1, there was the lowest incremental body weight.Keywords: Periodontitis, food pattern, weight growthABSTRAKLatar belakang: Model tikus yang mengalami periodontitis dengan inokulasi P. gingivalis dipilih untuk membuktikan bahwa kebutuhan energi pada periodontitis meningkat dan terjadi erosi massa tubuh yang mempengaruhi pertumbuhan. Tujuan penelitian adalah diperolehnya pola makan serta pertumbuhan bobot tubuh (BT) terendah, yang akan memberikan gambaran periode waktu pemberian zat-zat gizi untuk meningkatkan bobot tubuh guna mempercepat penyembuhan.Metode: Dilakukan studi eksperimental pada 63 ekor tikus Wistar jantan dewasa di Laboratorium Penelitian dan Pengujian Terpadu Universitas Gadjah Mada Yogyakarta tahun 2007-2008. Subyek studi diinokulasi dengan P. gingivalis hingga terjadi periodontitis. Penilaian periodontitis dengan pemeriksaan Patologi Anatomik dari sediaan jaringan periodontal. Pola makan yaitu persentase subyek dengan pakan habis terhadap keseluruhan subyek studi, sebelum dan selama periodontitis. Pertumbuhan BT adalah rerata bobot tubuh 2 periode periodontitis yang berurutan dibagi lama hari antara 2 periode tersebut.Hasil: Awal pakan habis dimulai dari teridentifikasinya periodontitis melalui pemeriksaan Patologi Anatomik. Besaran subyek dengan pakan habis bervariasi menurut proses periodontitis. Pertumbuhan BT sebelum dan selama periodontitis menunjukkan peningkatan dengan bertambahnya umur. Peningkatan rerata BT per hari menunjukkan nilai tertinggi pada periode sebelum periodontitis ke awal periodontitis. Nilai terendah peningkatan rerata BT terdapat pada awal periodontitis ke periode kronik 1, selama 7 hari.Simpulan: Subyek studi mulai menghabiskan pakan sejak dimulai periodontitis. Selama 7 hari dari awal periodontitis sampai periode kronik 1, terjadi peningkatan rerata BTterendah